The Impact of Organizational Culture on the Retention of Young Talents in the Regeneration Process in Diskomlekau Work Units - Setyanto, Achmad; Hadi Isnanto, Samto (Dinasti International Journal of Digital Business Management, 2025)
This research aims to identify the impact of organizational culture at Diskomlekau on the retention of young talent, which plays an important role in the process of organizational regeneration and sustainability. A qualitative descriptive approach was used in this research to collect and analyze data. Using a qualitative descriptive approach, this research found that organizational culture has a significant impact on the satisfaction and commitment of young employees. Positive values ??create a supportive work environment, but there are also pressures that can cause stress. Interview results show that an inclusive and innovative culture is attractive to young talents. This research emphasizes the important role of management in building a positive organizational culture. The results of the analysis show that organizational culture at Diskomlekau has a significant impact on the retention of young talent. Positive values ??in organizational culture create a supportive work environment, increasing the satisfaction and commitment of young employees. However, there are also challenges, such as pressure to contribute optimally which can cause stress. Young employees appreciate the culture that is inclusive and supports innovation, which is an attraction for them to continue working at Diskomlekau.